2019
DOI: 10.5194/isprs-archives-xlii-4-w15-11-2019
|View full text |Cite
|
Sign up to set email alerts
|

Semantically Enriched High Resolution Lod 3 Building Model Generation

Abstract: <p><strong>Abstract.</strong> This paper reports about an effort to generate LoD3 models of buildings semi-automatically, with the highest possible level of automation. It is work in progress. We use multi-sensor data like aerial images from a 5-head camera with a GSD of 10&amp;thinsp;cm, UAV images, and aerial and mobile LiDAR point clouds. We distinguish two cases: LoD2 models are available and they are not. We apply Multi-Photo Geometrically Constrained Least Squares Matching for diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Using different raw data from the latest technologies and methods (such as laser scanning, photogrammetry) and parametric modelling, geometrically correct façades can be generated and the accuracy or deviation of the models from reality can be determined. The process and the detailed contents of the research packages can be found under Gruen et al (2019).…”
Section: More Detailed Modelsmentioning
confidence: 99%
“…Using different raw data from the latest technologies and methods (such as laser scanning, photogrammetry) and parametric modelling, geometrically correct façades can be generated and the accuracy or deviation of the models from reality can be determined. The process and the detailed contents of the research packages can be found under Gruen et al (2019).…”
Section: More Detailed Modelsmentioning
confidence: 99%
“…There is a significant body of literature focused on trying to automate building model reconstruction to make it low-cost, faster, accurate and easy to update. Nevertheless, many of the approaches proposed to solve the challenge of automatic generation of detailed models require a great deal of pre-and post-processing, therefore restricting their utilisation as standalone solutions [9].…”
Section: Introductionmentioning
confidence: 99%
“…LiDAR technology has proven its usefulness in multiple fields, such as architecture, heritage and environment, among others (Refs. [6][7][8][9][10]), thanks to its great capacity to acquire massive data with geometric and radiometric information simultaneously. However, this productivity in the acquisition contrasts with the difficulty of its processing, since it requires extensive technical knowledge and a high computational cost.…”
Section: Introductionmentioning
confidence: 99%